2018
DOI: 10.1038/s41598-018-31283-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Maternal and Cord Antibodies Specific for Diphtheria, Tetanus, Pertussis, Measles, Mumps and Rubella in Shunyi, Beijing

Abstract: Maternal antibodies contribute to the protection of young infants from infectious diseases during the early life. However, vaccinations for women of child-bearing age are not routine in China. Therefore, we investigated the level of protective immunity against vaccine preventable diseases in pregnant women and newborns in China. A total of 194 paired maternal and cord blood samples were collected in Beijing from 2016 to 2017. Antibodies specific for the antigens covered by diphtheria-tetanus-pertussis (DTP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…This criterion is also in line with the manufacturer's instructions. The percentages of neonates from Shunyi with protective anti-Dtx (30.5%) and anti-Ttx (38.5%) IgG level were consistent with our previous studies among cord sera carried in Shunyi (a total of 38.7 and 26.8% of neonates had protection for diphtheria and tetanus) [12]. The prevalence of protective anti-Dtx and anti-Ttx IgG were lower in the neonates from Qianjiang (7.1% for anti-Dtx IgG and 7.6% for anti-Ttx IgG) than in those from Shunyi.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This criterion is also in line with the manufacturer's instructions. The percentages of neonates from Shunyi with protective anti-Dtx (30.5%) and anti-Ttx (38.5%) IgG level were consistent with our previous studies among cord sera carried in Shunyi (a total of 38.7 and 26.8% of neonates had protection for diphtheria and tetanus) [12]. The prevalence of protective anti-Dtx and anti-Ttx IgG were lower in the neonates from Qianjiang (7.1% for anti-Dtx IgG and 7.6% for anti-Ttx IgG) than in those from Shunyi.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the maternal antibody associated with DTP vaccine mainly depends on childhood immunizations and nature infections in China. According to our previous research, the prevalence of protective antidiphtheria (Dtx) and anti-tetanus (Ttx) IgG in cord sera were positively associated with pregnant women' birth places [12]. Anti-Ttx were used as an indicator of vaccination with tetanus toxoid-containing vaccine since natural immunity following tetanus disease does not occur as the quantity of tetanus toxin required to produce disease is inadequate to induce an immune response [1].…”
Section: Introductionmentioning
confidence: 99%
“…This gap in immunity is -at least in part -covered by the active, transplacental transfer of maternal pathogenspecific antibodies. Mothers convey passive immunity to their newborns through the transplacental transfer of antibodies, hereby providing a shield for the infant from pathogenmediated diseases (1,9). The amount of transferred antibodies can differ between individuals and is mainly dependent on maternal antibody concentrations (10,11).…”
mentioning
confidence: 99%
“…Maternal vaccination is the only time that vaccination can benefit two generations from a single input, with the possible exception of live polio vaccine [82]. A study in Beijing found that the seroprevalence of maternal and cord antibodies specific for diphtheria, tetanus, pertussis, measles, mumps, and rubella were lower than expected and the authors recommended a vaccination program before pregnancy [83]. Breastfeeding after maternal immunisation during pregnancy has been shown to promote transplacental IgG transfer and after birth, IgA is found in breastmilk.…”
Section: Maternal Vaccinationmentioning
confidence: 99%